Euryale Small Auxin Up RNA62 promotes cell elongation and seed size by altering the distribution of indole-3-acetic acid under the light - Huang, Zhi-heng; Bao, Ke; Jing, Zong-hui; Wang, Qian; Duan, Hui-fang; Zhang, Sen; Tao, Wei-wei; Wu, Qi-nan (Frontiers in Plant Science, 2022)
Euryale (Euryale ferox Salisb.) is an aquatic crop used as both food and drug in Asia, but its utilization is seriously limited due to low yield. Previously, we hypothesized that Euryale small auxin up RNAs (EuSAURs) regulate seed size, but the underlying biological functions and molecular mechanisms remain unclear. Here, we observed that the hybrid Euryale lines (HL) generate larger seeds with higher indole-3-acetic acid (IAA) concentrations than those in the North Gordon Euryale (WT). Histological analysis suggested that a larger ovary in HL is attributed to longer cells around. Overexpression of EuSAUR62 in rice (Oryza sativa L.) resulted in larger glumes and grains and increased the length of glume cells. Immunofluorescence and protein interaction assays revealed that EuSAUR62 modulates IAA accumulation around the rice ovary by interacting with the rice PIN-FORMED 9, an auxin efflux carrier protein. Euryale basic region/leucine zipper 55 (EubZIP55), which was highly expressed in HL, directly binds to the EuSAUR62 promoter and activated the expression of EuSAUR62. Constant light increased the expression of both EubZIP55 and EuSAUR62 with auxin-mediated hook curvature in HL seedlings. Overall, we proposed that EuSAUR62 is a molecular bridge between light and IAA and plays a crucial role in regulating the size of the Euryale seed.